решить, желательно развёрнуто
1) (1-cosx)(2-4sinx)=0
2) 2cos⁡ (3x+)=-1

veronikageletii veronikageletii    2   05.04.2020 06:57    1

Ответы
Jere558 Jere558  12.10.2020 15:22

вот думаю правильный ответ щя и второе попробую


решить, желательно развёрнуто 1) (1-cosx)(2-4sinx)=0 2) 2cos⁡ (3x+)=-1
решить, желательно развёрнуто 1) (1-cosx)(2-4sinx)=0 2) 2cos⁡ (3x+)=-1
решить, желательно развёрнуто 1) (1-cosx)(2-4sinx)=0 2) 2cos⁡ (3x+)=-1
решить, желательно развёрнуто 1) (1-cosx)(2-4sinx)=0 2) 2cos⁡ (3x+)=-1
решить, желательно развёрнуто 1) (1-cosx)(2-4sinx)=0 2) 2cos⁡ (3x+)=-1
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра